How Effective is Fiscal Policy Response in Systemic Banking Crises? - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2009)
This paper studies the effects of fiscal policy response in 118 episodes of systemic banking crisis in advanced and emerging market countries during 1980-2008. It finds that timely countercyclical fiscal measures contribute to shortening the length of crisis episodes by stimulating aggregate demand. Fiscal expansions that rely mostly on measures to support government consumption are more effective in shortening the crisis duration than those based on public investment or income tax cuts. But these results do not hold for countries with limited fiscal space where fiscal expansions are prevented by funding constraints. The composition of countercyclical fiscal responses matters as well for output recovery after the crisis, with public investment yielding the strongest impact on growth. These results suggest a potential trade-off between short-run aggregate demand support and medium-term productivity growth objectives in fiscal stimulus packages adopted in distress times.